2017
DOI: 10.5489/cuaj.4649
|View full text |Cite
|
Sign up to set email alerts
|

The risk of urinary retention following robot-assisted radical prostatectomy and its impact on early continence outcomes

Abstract: Introduction: We aimed to evaluate the risk factors of acute urinary retention (AUR) following robot-assisted radical prostatectomy (RARP), as well as the relationship of AUR with early continence outcomes. Methods: The records of 740 consecutive patients who underwent RARP by two experienced surgeons at our institution were retrospectively reviewed from a prospectively collected database. Multiple factors, including age, body mass index (BMI), international prostate symptom score (IPSS), prostate volume, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
(15 reference statements)
2
11
1
1
Order By: Relevance
“…Despite its larger costs, RARP has largely replaced the open approach, where available [10,11]. Improved visualization of the bladder neck and urethra during RARP led to decreased rates of VUA leakage as well as decreased rates of AUR, independent of time of catheter removal, compared to open surgery techniques [1,2,[12][13][14][15]. The major finding of our prospective study was that early catheter removal after RARP is feasible yet associated with a higher AUR rate.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Despite its larger costs, RARP has largely replaced the open approach, where available [10,11]. Improved visualization of the bladder neck and urethra during RARP led to decreased rates of VUA leakage as well as decreased rates of AUR, independent of time of catheter removal, compared to open surgery techniques [1,2,[12][13][14][15]. The major finding of our prospective study was that early catheter removal after RARP is feasible yet associated with a higher AUR rate.…”
Section: Discussionmentioning
confidence: 77%
“…Despite a considerable retention rate of 6.3% in our series, all patients were able to void spontaneously immediately after catheter removal. Some authors propose that AUR is due to edema of the VUA, an increased bladder neck muscle tone or postoperative pain [1,2,19,20]. Patel et al showed reduced AUR rates with Tamsulosin but the effect is likely to be dependent on the grade of bladder neck sparing [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other mechanisms such as increased bladder neck smooth muscle tone or pressure by surrounding hematoma have also been implicated in AUR after RARP. [ 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%